Avaliação da exposição ao ruído ocupacional em galpões de triagem de resíduos recicláveis - Schettini, Cristina Finger Lacerda (2014)
The assessment of occupational noise is important to prevent adverse effects and often damaging to the auditory system. This dissertation was based on a literature review which explained the definition of the sound and the measures used laws in force and applicable to assessment of noise and existence of unsanitary on this physical agent in two sheds sorting of recyclable waste. Initially the sound pressure measurements were performed in both houses which has two jobs each. The evaluated jobs were of the press operator and segregating waste. Each job was assessed during a 8 hours day. After tabulating the data dose estimates and equivalent level were performed, since the population was homogeneous adopted. The laws used for the methods and tolerance limits were: NHO01, Fundacentro and nr-15 from Ministry of Labour. Evaluating the results obtained by calculations carried out it is clear that both the jobs the activity developed is not unhealthy. Although the results show that employees are not exposed to harmful noise some samples were above 85 db (a) for this reason it is important to monitor the sound pressure emitted by vertical presses.So that health workers do not occur in future damages. Currently personal protection equipment are distributed to all members the problem is that not everyone uses this tool to protect themselves.